The effects of whole milk compared to skim milk and apple juice consumption in breakfast on appetite and energy intake in obese children: a three-way randomized crossover clinical trial - Kavezade, Shima (BMC Nutr, 2018)
BACKGROUND: A limited number of studies have examined the effect of dairy on satiety and short-term energy intake among children; furthermore we are not aware of any study comparing high and low-fat dairy products regarding their effect on appetite and short-term energy intake. Our objective was to assess the effect skim milk (SM) compared to whole milk (WM) and apple juice (AJ) on satiety and energy intake at lunch among 10–12 y children with obesity. METHODS: Fifty children with obesity who aged 10–12 y were randomized to consume a fixed content breakfast with 240 ml of SM, AJ, or WM for two consecutive days. The study was a three-way randomized crossover study; therefore each participant served as his/her own control. The total appetite, hunger, fullness, desire to eat and prospective consumption were measured using a visual analogue scale (VAS) before breakfast and every one hour after breakfast until a freely consumed lunch. VAS scores and energy intakes were compared using repeated measures procedure. RESULTS: Forty-eight participants (24 girls and 24 boys) completed the study. The energy intake was not different between SM, AJ and WM periods (adjusted mean ± standard error (SE) of energy intake: SM = 831.27 ± 30.64 Kcal, AJ = 794.92 ± 28.72 Kcal, WM = 798.87 ± 24.09 Kcal; P = 0.56). The effect was the same for either gender. Children reported higher satiety score 4 h after drinking WM with breakfast compared with SM (P < 0.05). The same association was found only in girls. Furthermore, SM significantly reduced appetite compared to AJ, 2 h after preloads in girls (P < 0.05). CONCLUSIONS: Full-fat milk may have favorable effects on satiety but not energy intake in subsequent meal compared to skim milk among the children with obesity. Future studies with longer follow-up periods are needed to confirm these results. TRIAL REGISTRATION: The study protocol was registered with the Iranian registry of clinical trials on 9th October 2016 (registration ID: IRCT2016072012571N5). ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40795-018-0253-8) contains supplementary material, which is available to authorized users.